Desenvolvimento de óvulo, fruto e semente de Xyris (Xyridaceae, Poales) - Nardi, Kaire de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Xyris is the largest genus of Xyridaceae, however there are few studies on its embryology and seed micromorphology. This thesis aimed to describe the development of ovule, fruit and seed of Xyris species in a comparative approach and to characterize the seed coat, identifying useful characters for taxonomy. The results show an embryological pattern for the genus: orthotropous, bitegmic and tenuinucellate ovules, with a micropyle formed by both the endostoma and exostoma; helobial, starchy endosperm; reduced, campanulate and undifferentiated embryo; seed coat formed by a tanniferous endotegmen, endotesta with thickwalled cells and exotesta with thin-walled cells; and a micropylar operculum. The pericarp is composed of a mesocarp with cells containing starch grains and an exocarp and endocarp formed by U-shaped thickened cells. The megagametophyte development differs among the studied species: it can be of the Polygonum or Allium type. The pericarp anatomy also varies since either the endocarp or the exocarp can have larger cells. The anatomy of the seed coat and pericarp in Xyris is first characterized here, as well as the origin of the operculum. Xyris differs from the other genera of Xyridaceae by the presence of orthotropous ovules, megagametophyte development of the Allium type, and seed coat composed of endotegmen, endotesta and exotesta, corroborating the division of the family into two subfamilies. The seed morphology and micromorphology show that the presence of longitudinal ridges in the seed coat is a pattern for the genus and that the following characters distinguish among the species: shape and size of the seed, shape of the ridges, number of cell rows between the ridges, and the striation pattern of the seed coat. Based on these characters a standard terminology is proposed to characterize the seed coat in the family

Xyris é o gênero mais representativo de Xyridaceae, porém há poucos dados disponíveis na literatura sobre sua embriologia e micromorfologia de sementes. O objetivo deste trabalho foi descrever o desenvolvimento de óvulo, fruto e semente de espécies do gênero em uma abordagem comparativa e caracterizar a superfície do envoltório seminal, com fins taxonômicos. Os resultados sugerem um padrão embriológico: óvulos ortótropos, bitegumentados e tenuinucelados, com micrópila formada pela endóstoma e exóstoma; endosperma helobial, amilífero; embrião reduzido, campanulado e indiferenciado; envoltório seminal formado por endotégmen taninífero, endotesta com células com espessamento de parede periclinal interna e exotesta formada por células de paredes finas; opérculo micropilar formado pelos tegumentos interno e externo. O pericarpo apresenta mesocarpo constituído por células contendo grãos de amido e exocarpo e endocarpo com células com espessamento de parede em “U”. Há diferenças quanto ao desenvolvimento do megagametófito, que pode ser do tipo Polygonum ou Allium, e também quanto ao pericarpo, que pode apresentar o endocarpo ou o exocarpo diferenciado. O desenvolvimento do envoltório seminal e do pericarpo é detalhado pela primeira vez, bem como a origem do opérculo. Xyris diferencia-se dos demais gêneros de Xyridaceae por apresentar óvulos ortótropos, desenvolvimento do megagametófito do tipo Allium e envoltório seminal constituído por endotégmen, endotesta e exotesta, corroborando a divisão da família em duas subfamílias. A morfologia e micromorfologia das sementes apontam a presença de cristas longitudinais como padrão para o gênero, além de indicar caracteres que permitem o reconhecimento das espécies como: forma e tamanho das sementes, forma das cristas, número de fileiras de células entre as cristas e padrão de estriação na zona entre cristas. A partir desse levantamento de caracteres...
Keywords: Plant anatomy; Anatomia vegetal; Embriologia; Botânica - Morfologia; Taxonomia vegetal; Sementes; Frutas; Ecologia vegetal; Xyridaceae